2014
DOI: 10.1002/2014wr015375
|View full text |Cite
|
Sign up to set email alerts
|

Optimal plant water‐use strategies under stochastic rainfall

Abstract: Plant hydraulic traits have been conjectured to be coordinated, thereby providing plants with a balanced hydraulic system that protects them from cavitation while allowing an efficient transport of water necessary for photosynthesis. In particular, observations suggest correlations between the water potentials at which xylem cavitation impairs water movement and the one at stomatal closure, and between maximum xylem and stomatal conductances, begging the question as to whether such coordination emerges as an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 70 publications
(111 reference statements)
1
51
0
Order By: Relevance
“…Abiotic effects encompass deep percolation and evaporation, as well as atmospheric conditions setting the rate of potential ET (i.e., the maximum rate of soil moisture decline). The biotic effects are primarily controlled by the shape of the Tmoisture curves, which depend on a suite of vegetation traits (Vico and Porporato 2008, Egea et al 2011, Manzoni et al 2014b). Therefore these curves should be interpreted as emerging properties of the internal dynamics in the plant-soil system, affected by plant functional traits and type (grasses, trees, shrubs), and by species adaptations.…”
Section: Dynamics Driven By External Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abiotic effects encompass deep percolation and evaporation, as well as atmospheric conditions setting the rate of potential ET (i.e., the maximum rate of soil moisture decline). The biotic effects are primarily controlled by the shape of the Tmoisture curves, which depend on a suite of vegetation traits (Vico and Porporato 2008, Egea et al 2011, Manzoni et al 2014b). Therefore these curves should be interpreted as emerging properties of the internal dynamics in the plant-soil system, affected by plant functional traits and type (grasses, trees, shrubs), and by species adaptations.…”
Section: Dynamics Driven By External Factorsmentioning
confidence: 99%
“…These trait-based, short-term models have been used to explore how different plant features determine emerging properties such as the transpiration-soil moisture and photosynthesissoil moisture relations at the daily time scale (Daly et al 2004a, b, Egea et al 2011, Manzoni et al 2014b. By linking aggregate parameters such as the moisture levels at incipient stomatal closure and at wilting, and the transpiration rate under well-watered conditions, to specific traits, these models bridge the gap between processbased representations and eco-hydrological models based on those aggregate parameters (e.g., Laio et al 2001.…”
Section: Modeling Plant Eco-physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Manzoni, et al [16] further demonstrated differences in K max , a, Ψ 50 , and normalized maximum transpiration rate with biome and growth form, similarly to Figure S8. A more complex mathematical framework revealed coordination between stomatal closure and Ψ 50 to reduce the risk of embolism while maintaining transpiration [67,68]. A number of smaller-scale, biome or growth form specific studies (e.g., [12,40,[69][70][71]) have revealed a number of more specific relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of ecohydrological parameters are relevant to a large range of applications for which the stochastic soil water 10 balance framework has been used and adapted, including: the effects of climate, soil and vegetation on soil moisture dynamics (Laio et al, 2001a;Rodrigues-Iturbe et al, 2001;Porporato et al, 2004), ecohydrological factors driving spatial and structural characteristics of vegetation (Caylor et al, 2005;Manfreda et al, 2017), soil salinization dynamics (Suweis et al, 2010), biological soil crusts (Whitney et al, 2017), vegetation stress, optimum plant water use strategies and plant hydraulic failure (Laio et al, 2001b;Manzoni et al 2014;Feng et al, 2017), vertical root distributions (Laio et al, 2006), plant 15 pathogen risk (Thomspon et al, 2013), streamflow persistence in seasonally dry landscapes (Dralle et al, 2016), and soil water balance partitioning (Good et al, 2014 ; http://rdcu.be/yqW7). A survey of close to 400 echoydrology publications found that 40% relied heavily on simulation, rarely integrated empirical measurements, and were almost never coupled with experimental studies, suggesting a critical need to combine modeling and empirical approaches in echohydrology (King and Caylor, 2011).…”
Section: Introductionmentioning
confidence: 99%